Draft Annual Plan 1996-97 Government of Mizoram - Planning Commission (Planning Commission, 1996)
Mizoram is the youngest State in India attaining the status of Statehood on 20th February, 1987. Mizoram occupies a very strategic position in the North Eastern corner of India having an international boundary of 487.65 Km and covers an area of 21,081 sq. km.
Government of Mizoram, Planning and Programme Implementation Department